An Overview of Social Support for Emerging Adults Who Have Lost a Parent Due to COVID-19: Penelitian - Aulia Arohadia Tusani; Luh Putu Ruliati; R. Pasifikus Ch. Wijaya; M. Dinah Charlota Lerik (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
This study aims to examine the profile of social support among emerging adults who have lost a parent to COVID-19. This study employed a qualitative descriptive method. Data were collected through in-depth interviews with seven participants in the emerging adulthood phase (aged 18–25 years), residing in Kupang City, who had lost a parent to COVID-19. The analytical technique used was Braun and Clarke's (2006) thematic analysis, consisting of six stages. The findings identified four main themes: (1) initial emotional reactions including shock, anger, and emptiness; (2) experiences of isolation in social relationships due to COVID-19 stigma; (3) forms of social support received, comprising emotional, instrumental, informational, and appraisal support, with the immediate family as the primary source; and (4) a gradual process of acceptance and recovery. A new finding in this study is the emergence of a spiritual support dimension not covered in Sarafino's theory, yet consistently meaningful within the religious cultural context of NTT society.